Determinants of Islamic Character Formation Among Students: The Role of The Merdeka Curriculum and Teacher Motivation - Titono Wahyudi; Amie Primarni; Yudi Permana (Jurnal Dirosah Islamiyah, 2026)
Islamic character education is a central objective of Islamic Religious Education, requiring alignment between curriculum policy and teacher-related factors. This study aims to examine the relationship and influence of Merdeka Curriculum implementation and teacher motivation on Islamic character education in Islamic Religious Education learning. The study employed a quantitative approach with a correlational research design. Data were collected through a structured questionnaire distributed to teachers of Islamic Religious Education at Islamic integrated elementary schools and analyzed using descriptive and inferential statistical techniques.The results indicate that the implementation of the Merdeka Curriculum and teacher motivation are positively and significantly related to Islamic character education. Partially, each independent variable has a significant influence on Islamic character education, while simultaneously, their combined contribution is stronger. These findings suggest that effective curriculum implementation supported by high teacher motivation plays a critical role in strengthening students’ Islamic character. This study highlights the importance of integrating curriculum policy and teacher motivation within a unified framework to optimize Islamic character education in Islamic Religious Education learning.